That's not my train-- : its wheels are too squashy - Watt, Fiona; Wells, Rachel (Tulsa, Okla. : Usborne, 2008)
A little mouse searches for his train, using textures to help him identify the right one.
Cover title.
On textured board pages.
1.3
K-3
Keywords: Mice -- Juvenile fiction; Railroad trains -- Juvenile fiction; Toy and movable books -- Specimens; Mice -- Fiction; Railroads -- Trains -- Fiction; Toy and movable books; Mice -- Fiction; Railroads -- Fiction; Toy and movable books